THE ROLE OF PARENTS IN FOSTERING SELF-CONFIDENCE FOR THE FISHERMEN’S’ CHILDREN STUDYING IN COLLEGE AT BANTAN AIR VILLAGE SUB-DISTRICT OF BANTAN THE REGENCY OF BENGKALIS - Wati, Miske; Irja, Desti; Achmad, Said Suhil (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
The purpose of study was to find out the role of parents in fostering self-confidence for the fishermen’s’ children studying in college at Bantan Air villagesub-district of Bantan the regency of Bengkalis. The right thing in the study wasthat the parents educated their children until college. The method used in the studywas descriptive and the population of study was parents numbering 30 parents.The writer did not take any sample because the population of study was not much.In collecting the data about the role of parents in fostering self-confidence for thefishermen’s’ children studying in college the writer used questionnaires directedto the respondents or parents. The data which have been collected were analyzedquantitative approach it was product moment correlation technique. Aftercollecting and analyzing the data the writer concluded that there was the role ofparents in fostering self-confidence for the fishermen’s’ children studying incollege at Bantan Air village sub-district of Bantan the regency of Bengkalis. Theanalysis resulted the statistic reliability with amount of 0.951. The score meansthe role of parents in fostering self-confidence for the fishermen’s’ childrenstudying in college. In other word, the better parents’ role and more the studentswill study in college.Keywords:1. The Role of Parents, 2. Fostering Self-Confidence, 3.Fishermen’s’ Children